Micro-credential course outline (Micro-Credential in Integrated and Sustainable Urban Farming: Plant Biology at Urban Farm ) - Amid, Azura (2021)
This module intends to increase learners’ knowledge on the importance of plant biology in the urban farm that will minimize the usage of chemical fertilizer and pesticides.